SAP30 Gene Is a Probable Regulator of Muscle Hypertrophy in Chickens - Petry, Bruna; Moreira, Gabriel Costa Monteiro; Copola, Aline Gonçalves Lio; Souza, Marcela Maria de; da Veiga, Fernanda Cristina; Jorge, Erika Cristina; de Oliveira Peixoto, Jane; Ledur, Mônica Corrêa; Koltes, James E.; Coutinho, Luiz Lehmann (Frontiers in Genetics, 2021)
Animals with muscle hypertrophy phenotype are targeted by the broiler industry to increase the meat production and the quality of the final product. Studies characterizing the molecular machinery involved with these processes, such as QTL studies, have been carried out identifying several candidate genes related to this trait, however, validation studies of these candidate genes in cell culture are scarce. The aim of this study was to evaluate SAP30 as a candidate gene for muscle development and to validate its function in cell culture in vitro. The SAP30 gene was down regulated in C2C12 muscle cell culture using siRNA technology to evaluate its impact on morphometric traits and gene expression by RNA-seq analysis. Modulation of SAP30 expression increased C2C12 myotube area, indicating a role in muscle hypertrophy. RNA-seq analysis identified several upregulated genes annotated in muscle development in treated cells (SAP30-knockdown), corroborating the role of SAP30 gene in muscle development regulation. Here, we provide experimental evidence of the involvement of SAP30 gene as a regulator of muscle cell hypertrophy.